Silver Diamine Fluoride: A Review - Osadolor, Obehi O.; Osadolor, Aisosa J. (Nepal Mediciti Medical Journal, 2023)
BACKGROUND The burden of untreated dental caries among African children is high. Silver diamine fluoride (SDF) is a simple, non- technique sensitive intervention to stop the progression of active untreated carious lesion in primary teeth among children. Silver diamine fluoride (SDF) 38% solution contains 44,800 ppm fluoride ions and its stains teeth after use. METHOD An electronic literature search in Web of science, Scopus, PubMed, Google Scholar, African journal online, Researchgate and Google was done in May,2023. Search terms and keywords were combined by Boolean operators. Two independent investigators (research assistants) screened titles, abstracts and full text of publications. The inclusion criteria were original research articles, case report, case series related to silver diamine fluoride ( human studies) conducted in African region and in electronic databases. RESULTS Ten articles were included as they were assessed to meet the aim of the review. The study design of the articles were four invitro studies, three randomized controlled clinical trial, one randomized clinical trial, one split-mouth, self-controlled clinical trial and one split-mouth, randomized controlled clinical study. 90 % of the studies identified was conducted in Egypt, while 10 % of the studies was conducted in Nigeria. CONCLUSION Studies on silver diamine fluoride (SDF) identified in African countries were few and restricted to few countries. Silver diamine fluoride can be used as an intervention for active and progressing untreated carious lesion in primary teeth among children though it stains teeth after use. More studies from the diverse ethnic population in Africa will contribute to the existing literature.